Barriers to Primary Care Clinician Adherence to Clinical Guidelines for the Management of Low Back Pain: A Systematic Review and Metasynthesis of Qualitative Studies. Issue 9 (September 2016) - Slade, Susan C.; Kent, Peter; Patel, Shilpa; Bucknall, Tracey; Buchbinder, Rachelle
Abstract : Introduction: Despite the availability of evidence-based guidelines for the management of low back pain (LBP) that contain consistent messages, large evidence-practice gaps in primary care remain. Objectives: To perform a systematic review and metasynthesis of qualitative studies that have explored primary care clinicians' perceptions and beliefs about guidelines for LBP, including perceived enablers and barriers to guideline adherence. Methods: Studies investigating perceptions and beliefs about LBP guidelines were included if participants were primary care clinicians and qualitative methods had been used for both data collection and analysis. We searched major databases up to July 2014. Pairs of reviewers independently screened titles and abstracts, extracted data, appraised method quality using the CASP checklist, conducted thematic analysis, and synthesized the results in narrative format. Results: Seventeen studies, with a total of 705 participants, were included. We identified 3 key emergent themes and 8 subthemes: (1) guideline implementation and adherence beliefs and perceptions; (2) maintaining the patient-clinician relationship with imaging referrals; and (3) barriers to guideline implementation. Clinicians believed that guidelines were categorical, prescriptive, and constrained professional practice; however, popular clinical practices superseded the guidelines. Imaging referrals were used to manage consultations and to obtain definitive diagnoses. Clinicians' perceptions reflected a lack of content knowledge and understanding of how guidelines are developed. Discussion: Addressing misconceptions and other barriers to uptake of evidence-based guidelines for managing LBP is needed to improve knowledge transfer and close the evidence-practice gap in the treatment of this common condition. Abstract : Supplemental Digital Content is available in the text.